Importancia de las semillas bio-activadas sobre las características agronómicas del cultivo de arroz (Oryza sativa L.). - Alava Huacon, Wilson Fernando (2022)
The main objective of the research was to establish the importance of bio-activated seeds on the agronomic characteristics of the rice crop (Oryza sativa L.). Seeds have the genetic potential of crops also carry large amounts of energy, which makes them very attractive to pests and diseases. Bioactivators are complex substances that allow enhancing and activating functions within the seed and plant, for a better protection against pests and diseases that cause the loss of yield and quality of the rice crop. The main bioactivators applied to rice seed are humic and fulvic acids, algae extracts, chitosans and beneficial fungi and bacteria that allow us to increase the efficiency of nutrient use and reduce the effects of different types of biotic and abiotic stresses. From the above, it has been concluded that there are bioactivators applied for the treatment of rice seeds, fulfilling important functions and ensuring germination, protection, nutrition, and stimulation for optimal growth and development of the crop.